Research on Human Capital Mismatching Measurement Based on Foreign Trade Intermediary Effects - Wei Wang, Yingzhe Wang (Forest Chemicals Review, 1970)
There are little of stocked and increased human capital in border area of Heilongjiang Province, because the development of social economy is unequal which causes attracting and focusing of talents are really weak. However, it leads to a low level about the necessary of human capital due to the poor economic base. As a result, people must consider whether the matching coordination between human capital and physical capital has some impact on human capital. Moreover, used mediating effect model verifies the transmission path. This essay demonstrate three aspects about these problems. Firstly, it measure the coupled coordination of human capital and physical capital in the border areas of Heilongjiang Province from 2006 to 2019. Most of them are judged to be in the range of 0.35 to 0.7, which shows that the coordination of human capital and physical capital matching is low not only in cities but also in counties. In addition, fixed-effects regression analysis is applied to verify that the coordination of human capital and physical capital matching in border areas of Heilongjiang Province has a significant positive effect on economic growth. Finally, a partial mediating effect is verified in a stepwise manner, where the human capital and physical capital match affects the economic growth rate through the mediating variable of foreign trade. Depending on these analyses, this essay mentions strategies which relate to the matching coordination between human capital and physical capital for the development of the population about trade with Russia. The purpose is that  rationalizing the flow of talents, optimizing the allocation of human resources, as well as reducing the degree of human capital mismatch.